An Updated Checklist on Fish Resources of Kali Estuary, Karwar, along the Southwest Coast of India - Shivakumar B Haragi; Sreekanth GB; Jagannath Rathod; Trivesh Mayekar; Akshata Naik; Rajeshree Pednekar; Sajiya Yusuf Mujawar (Journal of Indian Fisheries Association, 2020)
The present study aimed to analyse fish resources of Kali estuary based on the survey conducted during 2016 to 2020, along the central west coast of India, using the taxonomic, abundance, functional and feeding aspects. A total of 169 finfishes belonging to 56 families were recorded from the Estuary; among them, 110 were demersal and 59 pelagic species. The family Carangidae (21 species) contributed maximum number of species, followed by Sciaenidae (13), Leiognathidae (11), Ariidae (9), Engraulidae (7), Clupeidae (5), Gobiidae (5) and Mugilidae (5). The marine migrant species dominated the community, while the freshwater species contributed the least to the composition. This checklist provides comprehensive information about the finfish diversity in the Kali estuary that can be used for planning for conservation and management of these resources.